Foot Exercise to Overcome Type 2 Diabetes Mellitus: A literature Review - Ahmad Zakiudin; Gunawan Irianto; Asep Badrujamaludin; Hotma Rumahorbo; Susilawati Susilawati (Qualitative and Quantitative Research Center, 2022)
Prediction in 2030, the number of deaths due to Diabetes Mellitus (DM) will increase and become the seventh cause of death. The role of patients in managing DM is vital because DM is a chronic disease that will suffer for life. Foot exercise is one type of exercise to apply to DM patients. Diabetic foot exercise improves blood circulation and foot sensitivity. This study aims to inform readers about the effectiveness of foot exercise in overcoming DM type 2. This study is qualitative with a literature review. The analysis used inductive content to identify the main themes in the related literature. This article explores the indexed national and international journals of Scopus, Sinta, and Copernicus. There is an effect of diabetes mellitus foot exercise on improving the quality of life of patients with type 2 diabetes. Foot exercise provides comfort, reduces pain, and nerve damage, controls blood sugar, increases blood circulation in the feet, and improves symptoms of peripheral neuropathy such as tingling and numbness.